Direct Redox Sensing of Caffeine Utilizing Zinc-Doped Tin Oxide Nanoparticles as an Electrocatalyst - Gaurav Bhanjana; Ravinder Lamba; Manjit Singh Jadon; Neeraj Dilbaghi; Sandeep Kumar (BME Frontiers)
Objective: In addition to its positive benefits, caffeine also has harmful consequences. Therefore, it is essential to ascertain its content in various substances. Impact Statement: The present study emphasizes a novel way of quantification of caffeine in real as well as laboratory samples based on a nanomaterial-assisted electrochemical technique. Introduction: Electrochemical sensing is a prominent analytical technique because of its efficiency, speed, and simple preparation and observations. Due to its low chemical potential, SnO2 (tin oxide) demonstrates rapid redox reactions when used as an electrode. The presence of shielded 4f levels contributes to its distinctive optical, catalytic, and electrochemical capabilities. Methods: An efficient coprecipitation approach, which is simple and rapid and operates at low temperatures, is utilized to produce zinc-doped tin oxide nanoparticles (Zn–SnO2 nanoparticles). Zinc doping is used to modify the optoelectronic characteristics of tin oxide nanoparticles, rendering them very efficient as electrochemical sensors. Results: The crystal structure of samples was analyzed using x-ray diffraction, electronic transitions were calculated using ultraviolet–visible spectroscopy, and surface morphology was analyzed using field emission scanning electron microscopy. The x-ray diffraction investigation revealed that the produced Zn-doped SnO2 nanoparticles exhibit tetragonal phases, and the average size of their crystallites reduces upon doping Zn with SnO2. The bandgap energy calculated using the Tauc plot was found to be 3.77 eV. Conclusion: The fabricated caffeine sensor exhibits a sensitivity of 0.605 μA μM −1 cm−2, and its limit of detection was found to be 3 μM.